Recent Advances in Catalytic Asymmetric Aza‐Michael Addition Triggered Cascade Reactions - Song, Yong‐Xing; Du, Da‐Ming (Advanced synthesis & catalysis, 2021)
As an important branch of the Michael addition reaction, the aza‐Michael addition cascade reaction has been developed rapidly in recent years. This is because the reaction serves as an important method for effectively constructing functionalized C−N bonds, which can be widely used in the synthesis of chiral drugs and their intermediates and natural products. Given the importance of this topic, this review highlights the recent developments of aza‐Michael addition triggered cascade reactions in asymmetric synthesis, including aza‐Michael/Michael, aza‐Michael/Aldol, aza‐Michael/Henry, aza‐Michael/hemiacetal, aza‐Michael/Mannich, aza‐Michael/alkylation, aza‐Michael/cyclization, aza‐Michael/ring‐opening, aza‐Michael‐IED/HAD, aza‐Michael/INCR, and aza‐Michael/1,6‐conjugate addition reactions. In this paper, the reaction mechanism and derivatization experiments of different reactions are timely introduced to provide a more comprehensive theoretical basis for subsequent studies.